A Significant Portion of the Aequorin Luminescent Signal from Stimulated Human and Rabbit Platelets is Due to Exposure of the Aequorin to Calcium in the Suspending Medium - Vickers, John D; Perry, Dennis W (Thrombosis and Haemostasis, 1993)
We have examined in unstimulated and thrombin-stimulated human and rabbit platelets the localization and behavior of aequorin loaded by a variety of published methods. When platelets were suspended at 37° C in Tyrode-albumin medium containing 2 mM Ca2+ and apyrase, we found with all preparations that total aequorin revealed by addition of Triton X-100 decreased by more than 50% over one hour. Incubation in the presence of 5 mM EGTA followed by addition of Ca2+ to restore the concentration to 2 mM showed that some aequorin had entered the medium; subsequent addition of Triton X-100 showed that the increase in aequorin in the medium matched the decrease in aequorin in the platelets, such that total aequorin remained unchanged. However, comparison of aequorin in platelets incubated in media with and without Ca2+ showed a larger decrease in platelets incubated in the presence of Ca2+; this finding may indicate the presence of an intracellular pool of Ca2+ which is more dependent on external Ca2+. Stimulation of platelets with thrombin in the presence of EGTA resulted in a smaller luminescent signal than in the presence of Ca2+. Subsequent addition of Ca2+ to 2 mM in the platelet suspension that originally contained EGTA or to its supemate (after centrifugation of the platelet suspension), resulted in a larger luminescent signal compared with controls, indicating that stimulation of the platelets had increased loss of the aequorin into the medium. Together, these results indicate that a portion of the aequorin luminescent signal in stimulated platelets suspended in the presence of Ca2+ is due to loss of aequorin into the medium and thus results obtained under these conditions must be regarded with caution. The signal in platelets suspended in the absence of Ca2+ does appear to arise from aequorin inside the platelets.